6.9k views
5 votes
Use substitution to solve this system of the equations 2x-3y=-1 y=x-1

1 Answer

7 votes

Answer:

(x, y) = (4, 3)

Explanation:

The second equation gives an expression for y that can be substituted into the first equation.

... 2x -3(x -1) = -1 . . . . put x-1 where y was

... -x +3 = -1 . . . . . . . simplify

... 4 = x . . . . . . . . . . . add x+1

Using that second equation, we can find y to be ...

... y = 4 -1 = 3

The solution is (x, y) = (4, 3).

User Mital Joshi
by
5.8k points